A Drosophila screen identifies a role for histone methylation in ER stress preconditioning. - Owings, K.G.; Chow, C.Y. (G3 : genes - genomes - genetics, 2024)
Stress preconditioning occurs when transient, sublethal stress events impact an organism's ability to counter future stresses. Although preconditioning effects are often noted in the literature, very little is known about the underlying mechanisms. To model preconditioning, we exposed a panel of genetically diverse Drosophila melanogaster to a sublethal heat shock and measured how well the flies survived subsequent exposure to endoplasmic reticulum (ER) stress. The impact of preconditioning varied with genetic background, ranging from dying half as fast to 4 and a half times faster with preconditioning compared to no preconditioning. Subsequent association and transcriptional analyses revealed that histone methylation, and transcriptional regulation are both candidate preconditioning modifier pathways. Strikingly, almost all subunits (7/8) in the Set1/COMPASS complex were identified as candidate modifiers of preconditioning. Functional analysis of Set1 knockdown flies demonstrated that loss of Set1 led to the transcriptional dysregulation of canonical ER stress genes during preconditioning. Based on these analyses, we propose a preconditioning model in which Set1 helps to establish an interim transcriptional "memory" of previous stress events, resulting in a preconditioned response to subsequent stress.